2016
DOI: 10.2460/javma.248.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Survey of occupational hazards in Minnesota veterinary practices in 2012

Abstract: OBJECTIVE To identify the scope of occupational hazards encountered by veterinary personnel and compare hazard exposures between veterinarians and technicians working in small and large animal practices. DESIGN Cross-sectional survey. POPULATION Licensed veterinarians and veterinary staff in Minnesota. PROCEDURES A survey of Minnesota veterinary personnel was conducted between February 1 and December 1, 2012. Adult veterinary personnel working in clinical practice for > 12 months were eligible to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…One study of licensed clinical veterinarians in Minnesota and Wisconsin showed that almost 70% of veterinarians treated their injuries by either suturing lacerations, self‐prescribing antibiotics and even reducing their own fractures and/or dislocations [Landercasper et al, ]. More recently a study of clinical veterinary personnel in Minnesota found that up to 39% of respondents reported self‐medicating their injuries and illnesses, suggesting the pervasive and persistent nature of this behavior in the veterinary community [Fowler et al, ]. Similarly, occupational tasks associated with job titles may vary in terms of injury risk, with some higher risk tasks assigned to support personnel; this may explain some of the observed differences in claim rates between support staff and veterinarians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of licensed clinical veterinarians in Minnesota and Wisconsin showed that almost 70% of veterinarians treated their injuries by either suturing lacerations, self‐prescribing antibiotics and even reducing their own fractures and/or dislocations [Landercasper et al, ]. More recently a study of clinical veterinary personnel in Minnesota found that up to 39% of respondents reported self‐medicating their injuries and illnesses, suggesting the pervasive and persistent nature of this behavior in the veterinary community [Fowler et al, ]. Similarly, occupational tasks associated with job titles may vary in terms of injury risk, with some higher risk tasks assigned to support personnel; this may explain some of the observed differences in claim rates between support staff and veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies assessing occupational hazards in the veterinary setting however, suggest that physical trauma experienced from animal bites are the most common physical injury reported in the profession [Landercasper et al, ; Jeyaretnam et al, ; Gabel and Gerberich ; Fritschi et al, ]. One study of veterinary personnel in Minnesota found equal proportions of reported injuries in the previous 12 months among veterinarians and non‐veterinarian support staff [Fowler et al, ]. That study however did not include other animal care professionals in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the advent of surveillance systems to consistently and uniformly record injuries and illnesses among veterinary personnel will better characterize the hazards so that attention and resources can be prioritized for most effective risk reduction. 4,26,74,85 At present, best practices to mitigate these risks include environmental controls, written infection control policies that are consistently applied, staff training in the use of procedures and equipment to reduce risk, and use of appropriate personal protective equipment (eg, gloves, protective outerwear, and facial protection), with emphasis on groups that may be particularly vulnerable, such as pregnant women. 72,82,86,87 …”
Section: Resultsmentioning
confidence: 99%
“…could be the effect of increased awareness of veterinarians, and may be related to environmental studies focused on the occurrence of the above-mentioned pathogens. However, in literature, there are many examples of occupational exposure of veterinarians to these parasitic protozoans [14,15,16,17], and for a comprehensive assessment regarding to veterinarians in Poland, further study with a larger group of participants are needed. The basic method of stool examination in the present study was DFA, PCR was used only to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%